A case report of spontaneous bilateral perineal hematoma during pregnancy and literature review - Yu Wang; Hongchen Liu; Ye Lu (BMC Pregnancy and Childbirth)
Abstract Objective We report a rare case of spontaneous bilateral perineal hematoma during pregnancy. We analyze its etiology, clinical features, treatment, and prognosis to provide a reference for clinical practice. Methods Detailed clinical information was collected, including the patient’s pregnancy course, delivery process, imaging findings, and subsequent pregnancy outcomes. We discuss the potential mechanisms, management principles, and prognosis of spontaneous perineal hematoma during pregnancy in light of relevant literature. Results The patient began self-administered perineal massage at 36 weeks of gestation. At 39^+5 weeks, before delivery, bilateral spontaneous perineal hematomas developed. A left mediolateral episiotomy was performed during delivery. After conservative postpartum treatment, the hematomas gradually resolved, and the wound healed well. Eighteen months later, the patient had another vaginal delivery without reoccurrence of perineal hematoma or laceration. Conclusions Spontaneous perineal hematoma during pregnancy is rare. Its occurrence may be related to increased vascular fragility, venous congestion, and external forces. Although perineal massage in pregnancy may affect perineal tissues, there is no definitive evidence of a direct causal relationship with spontaneous hematoma. Proper guidance on correct technique and force is advised.